Factors associated with seizure and cognitive outcomes after epilepsy surgery for low-grade epilepsy-associated neuroepithelial tumors in children - Ara Ko; Joon Soo Lee (The Korean Pediatric Society, 2020)
Low-grade epilepsy-associated neuroepithelial tumors (LEATs) are responsible for drug-resistant chronic focal epilepsy, and are the second-most common reason for epilepsy surgery in children. LEATs are extremely responsive to surgical treatment, and therefore epilepsy surgery should be considered as a treatment option for LEATs. However, the optimal time for surgery remains controversial, and surgeries are often delayed. In this review, we reviewed published article on the factors associated with seizure and cognitive outcomes after epilepsy surgery for LEATs in children to help clinicians in their decision whether to pursue epilepsy surgery for LEATs. The achievement of gross total resection may be the most important prognostic factor for seizure freedom. A shorter duration of epilepsy, a younger age at surgery, and extended resection of temporal lobe tumors have also been suggested as favorable prognostic factors in terms of seizure control. Poor cognitive function in children with LEATs is associated with a longer duration of epilepsy and a younger age at seizure onset.